Modeling tsunami observations to evaluate a proposed late tsunami earthquake stage for the 16 September 2015 Illapel, Chile, Mw 8.3 earthquake - Thorne Lay; Linyan Li; Kwok Fai Cheung (Geophysical Research Letters)
Abstract Resolving seaward extent of slip during great subduction zone interplate ruptures using land‐based seismological and geodetic observations is challenging. Modeling of tsunami recordings from ocean‐bottom pressure sensors of the Deep‐ocean Assessment and Reporting of Tsunami (DART) network has added valuable constraints on near‐trench slip for recent events. We use DART and tide gauge recordings to evaluate a proposed seismological scenario involving a late Mw 8.08 tsunami earthquake following the ~95 s long main rupture stage of the 16 September 2015 Illapel, Chile, Mw 8.3 earthquake. Tsunami observations constrain the spatial extent of any late tsunami earthquake slip to locate north of the main shock hypocenter. The proposed late shallow slip predicts tsunami signals with considerable amplitudes but shorter wavelengths compared to those of the main stage slip constrained by joint seismic and tsunami modeling, yielding overprediction of first‐arrival amplitudes at DART and tide gauge stations when the two stages are combined.